BUDAYA ORGANISASI MEMODERASI PENGARUH MOTIVASI INTRINSIK DAN KECERDASAN EMOSIONAL TERHADAP KINERJA GURU MTs SEKECAMATAN WINONG KABUPATEN PATI - Sahlan, 1252020257; Sutomo, Yohanes (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to examine the effect of intrinsic motivation and emotional intelligence on the performance of teachers in MTs Sekecamatan Winong moderated Pati regency with organizational culture. The specific objectives of this study was to examine the effect of intrinsic motivation and emotional intelligence on the performance of teachers who are moderated by the role of organizational culture. The usefulness of this study is to clarify and extend previous research on the effect of intrinsic motivation and emotional intelligence on the performance of teachers who moderated the organizational culture. This study used a population of teachers in MTs Sekecamatan Winong Pati regency much as 173 teachers. Sampling techniques in this study is non probabilty sampling with purposive sampling method. The method used in this research is multiple regression with interaction quasi moderation. Based on the results of the study can be summarized as follows intrinsic motivation does not affect the performance of teachers, emotional intelligence does not affect the performance of the teacher, organizational culture does not affect the performance of the teacher, the influence of intrinsic motivation on teacher performance is moderated by organizational culture, and there is the influence of emotional intelligence on performance teachers are moderated by organizational culture. Keywords: emotional intelligence, organizational culture, intrinsic motivation, Performance teacher.